TRANSGENDER DAN REDEFINISI KHUNTSA DALAM KAJIAN MEDIS DAN FIQIH KONTEMPORER: STUDI KASUS APRILIO MANGANANG-AMAR ALFIKAR - Ahmad Asrof Fitri; Sansan Ziaul Haq (Asy-Syari'ah, 2022)
This research, which examines transgender and khuntsa in contemporary fiqh and medic, is inspired by the news on Aprilio Manganang and Amar Alfikar, who changed their gender due to medical and psychological problems. Aprilio was diagnosed with hypospadias, while Amar suffered from gender dysphoria. In classical fiqh literature, the concept of khuntsa is identified from a physical point of view only, which is generally categorized into khuntsa ghairu musykil if the person's gender can still be known and khuntsa musykil if the genitals cannot be ascertained after a medical research process. The purpose of this study is to determine the fiqh review of the transgender cases of Aprilio Manganang and Amar Alfikar. Using the library research method, this study finds that Aprilio is considered a khuntsa ghairu musykil because of hormonal and physical tendencies to men. While Amar, although born with female genital, gender dysphoria makes her feel that she is in an inappropriate body, thus causing self-harming. In the perspective of contemporary fiqh with psychological approach, the problem experienced by Amar require scholars to review the definition of khuntsa. The criteria of khuntsa musykil can be expanded by considering psychological disorders that arise from internal issues, not due to external influences.